The role of the voltage-gated potassium channel, Kv2.1 in prostate cancer cell migration - Park, Hyun Woo (BMB Rep, 2021)
Voltage-gated potassium (Kv) channels are involved in many important cellular functions and play pivotal roles in cancer progression. The expression level of Kv2.1 was observed to be higher in the highly metastatic prostate cancer cells (PC-3), specifically in their membrane, than in immortalized prostate cells (WPMY-1 cells) and comparatively less metastatic prostate cancer cells (LNCaP and DU145 cells). However, Kv2.1 expression was significantly decreased when the cells were treated with anti-oxidants, such as N-acetylcysteine or ascorbic acid, implying that the highly expressed Kv2.1 could detect reactive oxygen species (ROS) in malignant prostate cancer cells. In addition, the blockade of Kv2.1 with stromatoxin-1 or siRNA targeting Kv2.1 significantly inhibited the migration of malignant prostate cancer cells. Our results suggested that Kv2.1 plays an important role as a ROS sensor and that it is a promising therapeutic molecular target in metastasis of prostate cancer.